Defibrotide: potential for treating endothelial dysfunction related to viral and post-infectious syndromes. (3rd June 2021) - Richardson, Edward; García-Bernal, David; Calabretta, Eleonora; Jara, Rubén; Palomo, Marta; Baron, Rebecca M.; Yanik, Gregory; Fareed, Jawed; Vlodavsky, Israel; Iacobelli, Massimo; Díaz-Ricart, Maribel; Richardson, Paul G.; et al.
ABSTRACT: Introduction: Defibrotide (DF) is a polyribonucleotide with antithrombotic, pro-fibrinolytic, and anti-inflammatory effects on endothelium. These effects and the established safety of DF present DF as a strong candidate to treat viral and post-infectious syndromes involving endothelial dysfunction. Areas Covered: We discuss DF and other therapeutic agents that have the potential to target endothelial components of pathogenesis in viral and post-infectious syndromes. We introduce defibrotide (DF), describe its mechanisms of action, and explore its established pleiotropic effects on the endothelium. We describe the established pathophysiology of Coronavirus Disease 2019 (COVID-19) and highlight the processes specific to COVID-19 potentially modulated by DF. We also present influenza A and viral hemorrhagic fevers, especially those caused by hantavirus, Ebola virus, and dengue virus, as viral syndromes in which DF might serve therapeutic benefit. Finally, we offer our opinion on novel treatment strategies targeting endothelial dysfunction in viral infections and their severe manifestations. Expert Opinion: Given the critical role of endothelial dysfunction in numerous infectious syndromes, in particular COVID-19, therapeutic pharmacology for these conditions should increasingly prioritize endothelial stabilization. Several agents with endothelial protective properties should be further studied as treatments for severe viral infections and vasculitides, especially where other therapeutic modalities have failed.